Comparative Study on Anti-Acetylcholinesterase and Anti-Inflammatory Activities of Date and Apple Vinegars Fortified with Centella Asiatica - I Adenan, M; A Jusril, N; A Radzun, K; Z Hafiz, Z (International Journal of Engineering and Technology, 2019)
Neuroinflammation and deficiency of cholinergic are major factors of neurodegenerative damage correlated to cognitive impairment in Alzheimerâ€™s disease (AD). We investigated the anti-inflammatory and anti-acetylcholinesterase activities of apple and date vinegars added with Centella asiatica in SH-SY5Y neuroblastoma cells. The neuroprotective effect of apple or date vinegar added with various percentage of C. asiatica (0, 0.5, 2, 5) % w/v was determined in vitro. The methanolic extract of apple vinegar added with 2% C. asiatica (AV-2% CA) and date vinegar added with 2% C. asiatica (DV-2% CA) Â extracts showed potent neuroprotective effect. Both extracts were subjected to liquid-liquid partitioning yielded aqueous (H2O: AV/DV-2% CA) and ethyl acetate (EA: AV/DV-2% CA) extracts. Anti-inflammatory response against nitric oxide (NO) of all extracts was measured in LPS-induced SH-SY5Y neuroblastoma cells and percentage inhibition of acetylcholinesterase (AChE) was measured using commercially available test kits. It was found that EA: DV-2% CA showed potent ameliorating effect against LPS-induced inflammation (I50: 563.5 Â± 0.13Î¼g/mL) and was also responsible in the AChE inhibition activity (IC50: 9.087 Â± 0.02). Thus, this extract is suggested to have dual properties of anti-inflammatory and anti-acetylcholinesterase inhibition activity that could be beneficial in the treatment and prevention of neurodegenerative disease.Â Â Â